Gait Speed among Older Participants Enrolled in an Evidence-Based Fall Risk Reduction Program: A Subgroup Analysis - Cho, Jinmyoung; Smith, Matthew Lee; Shubert, Tiffany E.; Jiang, Luohua; Ahn, SangNam; Ory, Marcia G. (Frontiers in Public Health, 2015)
Background Functional decline is a primary risk factor for institutionalization and mortality among older adults. Although community-based fall risk reduction programs have been widely disseminated, little is known about their impact on gait speed, a key indicator of functional performance. Changes in functional performance between baseline and post-intervention were examined by means of timed up and go (TUG), a standardized functional assessment test administered to participants enrolled in A Matter of Balance/Volunteer Lay Leader (AMOB/VLL) model, an evidence-based fall risk reduction program. Methods This study included 71 participants enrolled in an AMOB/VLL program in the Brazos Valley and South Plain regions of Texas. Paired t-tests were employed to assess program effects on gait speed at baseline and post-intervention for all participants and by subgroups of age, sex, living status, delivery sites, and self-rated health. The Bonferroni correction was applied to adjust inflated Type I error rate associated with performing multiple t-tests, for which p-values <0.0042 (i.e., 0.5/12 comparisons) were deemed statistically significant. Results Overall, gait speed of enrolled participants improved from baseline to post-intervention (t = 3.22, p = 0.002). Significant changes in TUG scores were observed among participants who lived with others (t = 4.45, p < 0.001), rated their health as excellent, very good, or good (t = 3.05, p = 0.003), and attended program workshops at senior centers (t = 3.52, p = 0.003). Conclusion Findings suggest community-based fall risk reduction programs can improve gait speed for older adults. More translational research is needed to understand factors related to the effectiveness of fall risk reduction programs in various populations and settings.